Autocatalytic photodegradation of [Ru(ii)(2, 2′-bipyridine)2DAD]+ (DADH = 1, 2-dihydroxyanthracene-9, 10-dione) by hydrogen peroxide under acidic aqueous conditions. Issue 22 (11th May 2021) - Zeng, Lingli; Sirbu, Dumitru; Tkachenko, Nikolai V.; Benniston, Andrew C.
Abstract : An autocatalytic photoinitiated reaction helps decomposition of the alizarin-based ruthenium(ii ) bipyridine complex in the presence of hydrogen peroxide. Abstract : As part of a continuing effort to identify ruthenium agents capable of the photorelease of anthraquinone-based ligands the complexes Δ/Λ-[Ru(bpy)2 DAD] + (bpy = 2, 2′-bipyridine) were produced by the reaction of 1, 2-dihydroxyanthracene-9, 10-dione (DADH) with chirally pure Δ/Λ-[Ru(bpy)2 (py)2 ][(+)- O, O ′-dibenzoyl-d -tartrate]·12H2 O (py = pyridine). A very subtle difference in the chemical shift of the hydroxyl proton in their high-field 1 H NMR spectra was observed, supporting that the OH proton is susceptible to a small change in environment at the metal centre. The excited state lifetime of the complexes, as measured by femtosecond pump–probe spectroscopy, was 7.1 (±0.8) ps in water (pH 2) and 13 (±1) ps in MeCN. Illumination of a sample of Λ-[Ru(bpy)2 DAD] + in water (pH 2) in the presence of hydrogen peroxide resulted in decomposition of the complex. The decay profile, as monitored at several wavelengths, was sigmoidal indicating the reaction was autocatalytic, in which the product formed catalysed decomposition of the starting complex. A mechanism is proposed that relies on participation of the uncoordinated hydroxyl group on the anthraquinone ligand in promoting water loss and radical formation in the excited state. The radical is oxidised by peroxide to generate the ruthenium(iii ) complex, which behaves as an oxidant in the autocatalytic process.